Essays on Paula Rego - Manuel Lisboa, Maria (Open Book Publishers, 2021)
In these powerful and stylishly written essays, Maria Manuel Lisboa dissects the work of Paula Rego, the Portuguese-born artist considered one of the greatest artists of modern times. Focusing primarily on Rego’s work since the 1980s, Lisboa explores the complex relationships between violence and nurturing, power and impotence, politics and the family that run through Rego’s art.